Standards of Competence for Hydrographic Surveyors - Kapoor, D. C. (The International Hydrographic Review, 2015)
In presenting the Report of the International Advisory Board on Training, I propose to outline some of the principles and concepts that contributed towards the development of the syllabi and the accompanying guidelines issued as the IHO-FIG “ Standards of Competence for Hydrographic Surveyors” . I shall also endeavour to present some thoughts on how the Advisory Board envisages the future implementation of these international standards.